Sex-Specific Differences in Nutrient Intake in Late Preterm Infants - Pradeep Alur; Sumana Ramarao; Addie Hitt; Simmy Vig; Radha Alur; Naveed Hussain (MDPI AG, 2024)
Challenging the assumption of uniform nutritional needs in preterm feeding, this study identifies crucial sex-specific disparities in formula milk intake and growth among late preterm infants. Premature infants have difficulty regulating their oral intake during feeds, which is why clinicians prescribe feeding volume, calories, and protein via the nasogastric route. However, premature male and female infants have different body compositions at birth, and, subsequently, there is no evidence to suggest that male and female preterm infants differ in their nutritional consumption once they begin feeding ad libitum. This study investigates whether there are any differences in the volume and nutrient intake between the sexes when fed formula ad libitum. Methods: The study involved a retrospective analysis of preterm infants admitted to the NICU and evaluated between 34 0/7 and 36 6/7 weeks of corrected gestation. Late preterm infants appropriate for gestational age who were spontaneously fed formula milk ad-lib and free of any respiratory support for at least two days were included. The study excluded infants with short gut syndrome, severe chromosomal anomalies, or congenital heart conditions. We included 85 male and 85 female infants in this study. The data collected included sex, gestational age, birth weight, anthropometric data at birth, maternal data, nutritional intake, and neonatal morbidity. Results: This study found that female infants consumed more volume, protein, and calories than male infants. The mean formula intake in female and male infants was 145.5 ± 20.8 mL/kg/d and 135.3 ± 19.3 mL/kg/d, respectively, with p = 0.002. However, ad-lib feeding duration was not different between the sexes. Growth velocity was also higher in female infants. Conclusions: This study is the first to demonstrate differences in formula milk intake among late preterm infants fed ad libitum. Additional research is needed to confirm our findings and understand sex-specific differences in neonatal nutrition in extremely early preterm infants.